Study on chemoprevention of hepatocellular carcinoma by ginseng: an introduction to the protocol. (Korean Academy of Medical Sciences, 2001)
In patients with chronic hepatitis C virus disease, there is a high incidence of development of hepatocellular carcinoma (HCC) in the process of transition from chronic hepatitis to hepatic cirrhosis. Although ginseng traditionally has been used mainly as a nutritional supplement in Asian countries, a case-control study found that it may inhibit the development of HCC. We therefore planned a clinical study of HCC prevention by medicinal ginseng. The subjects are patients with chronic C virus disease (chronic hepatitis and hepatic cirrhosis), who are high risk group for HCC. This intervention study is a multi-center, double-blind, randomized controlled trial. The participants will be randomly divided into two groups. The test sample (1 g of red ginseng powder per day) will be administered for 5 yr, and ginseng intake will be prohibited during the administration period. The primary endpoint of this study is the development of HCC. Target number of recruiting subjects are 300. The participants should be registered from February 2001 to January 2003.